Thrombolytic and Pharmacokinetic Properties of Human Tissue-Type Plasminogen Activator Variants, Obtained by Deletion and/or Duplication of Structural/Functional Domains, in a Hamster Pulmonary Embolism Model - Collen, D; Lijnen, H R; Vanlinthout, I; Kieckens, L; Nelles, L; Stassen, J M (Thrombosis and Haemostasis, 1991)
A pulmonary embolism model in hamsters was used for the quantitative evaluation of the thrombolytic and pharmacokinetic properties of variants of tissue-type plasminogen activator (t-PA). A 25 μi 125I-fibrin labeled human plasma clot was made in vitro and injected into the jugular vein of heparinized hamsters. The extent of thrombolysis within 90 min was determined as the difference between the radioactivity injected in the jugular vein and that recovered in the heart and lungs.Recombinant t-PA (home-made rt-PA or Activase®) infused intravenously over 60 min caused dose-dependent progressive thrombolysis. The results of thrombolytic potency (clot lysis in percent versus dose administered in mg/kg) and of specific thrombolytic activity (clot lysis in percent versus steady state plasma level in μg/ml) were fitted with an exponentially transformed sigmoidal function y = 100 c/(1+e−a(ex−eb)) and the maximal percent lysis (c), the dose or plasma level at which maximal rate of lysis is achieved (b) and the maximal rate of lysis (z = ¼ ac .eb) were determined. With rt-PA, these parameters were c = 72 ± 6% (mean ± SEM), b = 0.19 ± 0.08 mg/kg, z = 68 ± 25% lysis per mg/kg, with corresponding values of 87 ± 5%, 0.07 ± 0.03 mg/kg and 150 ± 38% lysis per mg/kg for Activase® (p = NS). Deletion of the finger and growth factor domains in rt-PA ( rt-PA-ΔFE) was not associated with marked alteration of the thrombolytic potency (c = 90 ± 30%, b = 0.34 ± 0.35 mg/kg, and z = 54 ± 14% per mg/kg), but was associated with a significant reduction of the specific thrombolytic activity. Substitution of the kringle 1 domain by a second copy of the kringle 2 domain in rt-PA and in rt-PA-ΔFE did not significantly alter the thrombolytic potency as characterized by a simultaneous decrease of the b value and an increase of the z value (b = 0.07 ± 0.03 mg/kg and z = 210 ± 70% per mg/kg for rt-PA-ΔK1∇K2 and b = 0.13 ± 0.02 mg/kg and z = 210 ± 29% per mg/kg for rt-PA-ΔFEK1∇K2). Deletion of either the finger or the growth factor domain in rt-PA-ΔK1∇K2 also did not significantly alter the thrombolytic potency (b = 0.08 ± 0.008 mg/kg and z = 320 ± 33% per mg/kg for rt-PA-ΔEK1∇K2 and b = 0.05 ± 0.01 mg/kg and z = 270 ± 48% per mg/kg for rt-PA-ΔFK1∇K2). Likewise, none of the variants had a higher specific thrombolytic activity than wild-type rt-PA. Plasma clearance rates were reduced 10- to 20-fold for the rt-PA mutants lacking the FE domains, and 3- to 5-fold for rt-PA-ΔK1∇K2.